An Economic Model for the Revamping of a Pulverized Coal-fired Boiler - Cetin, B. (TAYLOR & FRANCIS INC, 2014)
Equipping existing thermal power plants (TPPs) with newer technologies, such as fluidized bed combustion (FBC), is vital for many countries due to concerns about the economy, the environment, and energy policy. First, this study presents a general model for economic analysis of the revamping of a pulverized coal-fired boiler with FBC. Second, the developed model is applied to a 140 MW pulverized coal-fired TPP. Third, the payback period (PBP) is calculated by using the net present value (NPV) method. Finally, the effects of almost all technical and economic parameters, such as power loss, electricity price, and escalation rate are investigated on PBP and NPV. As a result, the outcomes of this study show that power loss has a significant effect on PBP and NPV.
Keywords: boiler revamping; economic analysis; payback period; thermal power plant; COMBUSTION; Energy & Fuels